SEVERE FORM OF ATOPIC DERMATITIS AS A THERAPEUTIC CHALLENGE - Janja Golobič; Gašper Markelj (The Society for Children with Metabolic Disorders, 2022)
Atopic dermatitis (AD) is the most common chronic inflammatory skin disease of childhood. The disease is characterized by recurrent eczematoid itchy skin lesions caused by a combination of genetic predisposition and environmental factors (1-2). The disease usually appears in the first year of life and its course is generally mild, although occasionally, due to the intensity of the disease, treatment with systemic immunosuppressive drugs is required. (1-3, 7). In this paper, we present the case of an 8 - year - old boy with severe atopic dermatitis that could not be controlled with local therapy. With cyclosporin treatment at the desired therapeutic level of the drug, the disease subsided, and the number of bacterial superinfections and herpes simplex virus infections decreased. With long-term treatment, good attenuation of skin inflammation was achieved and cyclosporin treatment was successfully discontinued.